2016
DOI: 10.1080/02786826.2016.1254721
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lung volume during imaging on CFD within realistic airway models

Abstract: In this article, we address a fundamental question regarding computational fluid dynamics (CFD) modeling within lung airways: does the inhaled volume during imaging have a significant effect on CFD computations of aerosol deposition? High resolution computed tomography (HRCT) images taken at mean lung volume (MLV) and at total lung capacity (TLC) obtained as part of a previous study of ventilation and aerosol deposition using positron emission tomography (PET) in challenged asthmatics were utilized to construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Alzahrany et al [ 27 ] found that the orientation of endotracheal tube determines the local and total deposition. Katz et al [ 28 ] considered the influence of lung volume during imaging on PD.…”
Section: Introductionmentioning
confidence: 99%
“…Alzahrany et al [ 27 ] found that the orientation of endotracheal tube determines the local and total deposition. Katz et al [ 28 ] considered the influence of lung volume during imaging on PD.…”
Section: Introductionmentioning
confidence: 99%
“…This misconception has recently been recognized by researchers using such models of the lung. For example, in a CFD study on aerosol deposition in bronchial tree models extracted from HRCT images at MLV and TLC, Katz et al [ 27 ] concluded that lung volume should be explicitly considered when using deposition models. Bordas et al [ 21 ], lacking relevant information for a population of asthmatic patients, used the minimum inner diameters of the segmented airways in conjunction with a circular cross-section assumption to predict airflow in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling of the lungs has become an important tool for both diagnostic [ 1 – 4 ] and research [ 5 11 ] purposes. Functional features of the lung such as airway compliance or distensibility [ 12 15 ], resistance [ 9 , 12 , 16 21 ], aerosol deposition [ 5 , 9 , 22 27 ] and ventilation distribution [ 10 , 19 , 26 , 28 32 ] computations are frequently made using a combination of medical images and the utilization of such models. Clearly, knowledge of the underlying lung morphologies is a key to these applications.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the above might be due to the variation in the drug deposition due to (a) patient‐specific differences in the lung dimensions, (b) drug inhaler usage, (c) variability in liver/kidney clearances, and (d) change in the lung morphology, due to the severity and type of the disease (for instance, certain asthma attacks and Chronic obstructive pulmonary disease (COPD) conditions are characterized by highly localized blockages that heavily affect the flow of gas and drug particle deposition in these regions). To address the first source of variation, researchers have been developing tools, for the generation of the population‐ and subject‐specific virtual airway anatomical and computational aerosol inhalation and deposition models based on anthropometric data and physiological vitals . When combined with inhalation topography, such models are invaluable in respiratory diagnostics, personalized pulmonary pharmacology, and model‐based management of chronic respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to develop 3D models for computational fluid dynamics (CFD) calculations of aerosol transport and deposition based on these morphometric models. The converse is also possible, that is, the use of 3D models acquired through medical imaging modalities for the development of morphometric models of the lung or the direct simulation of gas and aerosol transport and deposition on such models …”
Section: Introductionmentioning
confidence: 99%